Formation and metamorphism of aluminous upper mantle and lower crustal rocks: a case study on websterite and granulite xenoliths from basanites of the Chyulu Hills volcanic field, Kenya - Ulianov, Alexey (My University, 2005)
The Chyulu Hills volcanic field is located on the eastern flank of the Kenya rift some 150 km to the east of the Kenya Rift Valley. It lies on the Pan-African crystalline basement of the Mozambique mobile belt. Quaternary basanites of the Chyulu Hills contain peridotite, pyroxenite and granulite xenoliths entrained from the underlying upper mantle and lower crust. This study focuses on a suite of garnet-spinel olivine websterite, Mg-Al sapphirine-bearing and Ca-Al hibonite-bearing granulite xenoliths from several volcanic cones of the Chyulu Hills. In terms of protoliths, they form an igneous suite linked by fractionation. High bulk rock Mg#’s and very low concentrations of most incompatible elements indicate that the rocks represent a sequence of cumulates rather than crystallized melts. The websterites are the most magnesian part of this sequence, while the granulites are less magnesian and more rich in aluminum, calcium and alkalis. Along with constraints from postmagmatic P-T evolution, low HSFE abundances, LILE enrichment and fractionation of LREE over HREE in whole rock samples suggest that the protoliths of the xenoliths may represent arc cumulates, which implies that they should be of Pan-African age. The normative compositions of the granulites are dominated by plagioclase and olivine. This, as well as the elevated abundances of Ni, low concentrations of Cr and HFSE and positive Eu anomalies in REE patterns suggests that the protoliths of the granulites were troctolitic cumulates. The original mineral assemblages were almost completely transformed by subsolidus processes. Mg-Al granulites contain the minerals spinel, sapphirine, sillimanite, plagioclase, corundum, clinopyroxene, orthopyroxene and garnet, while Ca-Al granulites are characterized by hibonite, spinel, sapphirine, mullite, sillimanite, plagioclase, quartz, clinopyroxene, corundum, and garnet. In the Mg-Al granulites, the first generation of orthopyroxene and some spinel may be of igneous origin. In the Ca-Al granulites, hibonite (and eventually some spinel) are the earliest mineral in the crystallization sequence and may represent igneous relicts. Most pyroxene and spinel as well as corundum in both Mg-Al and Ca-Al granulites have formed by subsolidus reactions. The qualitative P-T path derived from metamorphic reactions corresponds to subsolidus cooling accompanied or followed by compression. Final equilibration was achieved at T ≈ 600-740 oC and P < 8 kbar, the pressure range being constrained by the stability of sillimanite. The early coexistence of corundum and pyroxenes (± spinel) as well as the association of sillimanite and sapphirine with clinopyroxene and the occurrence of hibonite makes both types of the studied granulite lithologies rare. The Ca-Al hibonite-bearing granulites are unique. Both types enlarge the spectrum of known Ca-Al-Mg-rich granulites worldwide. Hibonite found in two xenoliths of the Ca-Al granulites occurs as small grains in the inner parts of complex corona textures where it forms intergrowths with spinel and sapphirine and shows reaction relationships with later mullite and sillimanite. Chemically, the analyzed hibonite is close to the idealized formula Ca(Al,Cr,Ti,Si,Mg,Fe2+)12O19 and does not contain other major components. It is similar to terrestrial hibonite in its (Fe+Mg) contents but shows the elevated Al and Ca abundances as well as the relative depletion in Ti and REE typical of meteoritic hibonite. Silica contents are high and exceed those in any other terrestrial and meteoritic hibonite. In order to evaluate the possibility of magmatic crystallization of hibonite in the igneous protoliths of the studied rocks, we compare some of the measured element abundances with those expected from element partitioning data for hibonite and Ca,Al-rich silicate melt. Based on this comparison, formation of low-Ti hibonite that is relatively rich in LREE appears consistent with magmatic crystallization, whereas hibonite with elevated Ti contents, low in LREE, is obviously the result of diffusion re-equilibration in the course of subsolidus cooling. For the websterite xenoliths, there is an apparent contradiction between the textural-mineralogical data and results of P-T calculations that appear to suggest high-P igneous crystallization of pyroxenes under upper mantle conditions on the one hand and the positive Eu anomaly that suggests shallow-level plagioclase accumulation on the other hand. This contradiction can in part be reconciled by a model of compression of a plagioclase-bearing (gabbroic) protolith at near-igneous temperatures to mantle depth where it obtained its ultramafic phase assemblage. This would require foundering of dense lower crustal material into the mantle towards the end of Pan-African subduction and accretion, a process that is possible in areas with high geothermal gradients such as arcs. The subsequent P-T evolution of the websterites as well as of most other types of upper mantle xenoliths from the Chyulu Hills is defined by a long period of cooling that may in some specimens be followed by (a) recent heating event(s). The chemical zoning patterns of orthopyroxene are either flat (suggesting complete subsolidus diffusion reequilibration) or show a core-to-rim decrease of Al and Ca indicating cooling. In both cases, Al and Ca may show a rimwards increase in the outermost zones of the orthopyroxene grains that is consistent with heating. Results from diffusion modeling for pyroxenes, albeit highly approximate, suggest that the rimwards increase in Al and Ca associated with heating is temporally related to the young volcanic activity of the Chyulu Hills, whereas the duration of cooling is much longer and may correspond to the age of the Pan-African orogeny (ca. 600 Ma). Pressure-temperature data on equilibrated xenoliths suggest a geotherm beneath the Chyulu Hills similar to a ~ 60–70 mW m-2 steady-state model geotherm. The lithospheric thickness is constrained to ca. 115 km. The late heating affected xenoliths derived from depths of ca. 80-40 km. It represents a local feature most probably related to small magma intrusions in the lithospheric mantle.
Thèse de doctorat : Université de Neuchâtel, 2005 ; 1861
Keywords: manteau supérior, croûte inférieure, xénolithes, série magmatique, métamorphisme, troctolite, websterite, granulite, sapphirine, hibonite, Mozambique orogène, Les Chyulu Hills, Kenya; upper mantle, lower crust, xenoliths, magmatic series, metamorphism, troctolite, websterite, granulite, sapphirine, hibonite, Mozambique mobile belt, Chyulu Hills, Kenya